Plexiform or multinodular schwannoma of posterior tibial nerve: case report with review of literature - Singhi, Prahalad Kumar; Raju, Sivakumar; V., Somashekar; Kumar, Bharat; Kumar, Anil (International Journal of Research in Orthopaedics, 2020)
A schwannoma is a benign tumor that develops from the Schwann cells, which assists conduction of nerve impulses and located in the nerve sheath of peripheral or cranial nerves. Plexiform or multinodular Schwannoma of posterior tibial nerve is a rare presentation, can cause diagnostic dilemma with Lumbosacral radiculopathy, Tarsal tunnel syndrome, Entrapment neuropathy or Chronic regional pain syndrome. Unexplained leg pain, a positive Tinel’s sign with or without a palpable swelling and Magnetic Resonance Imaging will clinch the diagnosis after excluding other causes. In symptomatic cases with long standing complaints, surgical resection yields satisfactory outcome. We present an interesting case of plexiform schawannoma along posterior tibial nerve with review of literature.